2019
DOI: 10.1111/acer.14191
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Associations between Sleep, Intrusive Thoughts, and Alcohol Problems Among Veterans

Abstract: Background: Research suggests bidirectional associations between symptoms of posttraumatic stress disorder (PTSD) and sleep disturbance, both of which have been associated with alcohol problems. However, few studies have examined the interplay of these conditions in predicting alcohol problems over time. This study tested 2 competing models: (i) sleep disturbance as a mediator of the association between intrusive thoughts about trauma and alcohol problems and (ii) intrusion symptoms as the mediator of the slee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 54 publications
(61 reference statements)
1
4
0
Order By: Relevance
“…In addition, we found thought suppression as a potential risk factor of depression. This finding is consistent with the Ironic Process Theory (Beevers et al, 1999 ) and previous literature where depressed individuals suppressing their thoughts tend to have worsening depression symptoms (Miller et al, 2019 ; Wenzlaff et al, 2001 ). Again, this requires confirmation via an experimental/longitudinal design.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, we found thought suppression as a potential risk factor of depression. This finding is consistent with the Ironic Process Theory (Beevers et al, 1999 ) and previous literature where depressed individuals suppressing their thoughts tend to have worsening depression symptoms (Miller et al, 2019 ; Wenzlaff et al, 2001 ). Again, this requires confirmation via an experimental/longitudinal design.…”
Section: Discussionsupporting
confidence: 92%
“…Duran and Woodhams ( 2022 ) found that analytical practitioners cope with the nature of their work by actively suppressing unwanted intrusive thoughts related to traumatic material when they come to mind. However, in the literature (Ehlers & Clark, 2000 ), this is considered maladaptive because the suppression of recollections of the traumatic event can increase the likelihood of them coming back to mind (Miller et al, 2019 ). Thought suppression could be a protective factor when stress levels are low, but it could be a risk factor when life stress increases.…”
mentioning
confidence: 99%
“…Intrusive thoughts and hyperarousal, however, remained significantly associated with childhood emotional and physical abuse in the military trauma group. Among veterans, PTSD's intrusive thoughts are associated with more alcohol problems (Miller et al, 2019) and hypervigilance is associated independently with both PTSD and military deployment (Kimble et al, 2013). In contrast with the military trauma group, the civilian trauma group showed no significant symptom cluster associations with childhood physical abuse, instead expressing the range of symptoms in association with childhood emotional and sexual abuse.…”
Section: Discussionmentioning
confidence: 81%
“…Some participants volunteered coping strategies that could be maladaptive. For example, some used thought suppression to cope and models of PTSD (e.g., Ehlers and Clarke 2000) caution that such methods could exacerbate PTSD-like symptoms such as intrusive thoughts (Birrer et al 2007;Miller et al 2019). Similarly, emotional detachment and processing material at a shallow level could aggravate PTSD-like symptoms as they prevent sufficient processing of the traumatic material to avoid or escape the fear (Shay and Munroe 1999).…”
Section: Discussionmentioning
confidence: 99%